THE RELEVANCE OF THE SHORT STORY SYAMSYUN AL-JABBAR TO THE NARRATIVE OF PROPHET SYAM'UN: A NEW HISTORICISM STUDY - ِAinia Fatma Afita Sari; Farhah, Eva; Sausa, Luigi (Journal of Arabic Language and Literature (ALLAIS), 2024)
This study examines the relevance of characterization and plot in the short story Syamsyun Al-Jabbar by Kamil Kilani to the historical narrative of Prophet Syam’un using a New Historicism approach. The research aims to reveal the similarities and connections between the narrative elements of the short story and the historical account of Prophet Syam’un, which remains relatively unknown to the public. Data for this study were collected through library research by analyzing the short story Syamsyun Al-Jabbar and various historical sources documenting the life of Prophet Syam’un. The study employs a qualitative method with parallel analysis, comparing the text of the short story with historical sources. The findings reveal the relevance of the character Syamsyun to Prophet Syam’un, Dalilah to the Prophet's wife, and Sultan to the disbelievers, along with a parallelism in the plot comprising four main stages. In conclusion, the short story Syamsyun Al-Jabbar symbolically represents the history of Prophet Syam’un, emphasizing his existence in a way that highlights his underappreciated historical significance.